Strategi Peningkatan Kesadaran Produk Berbasis Kelor (M. Oleifera) Melalui Kesadaran Masyarakat atas Stunting yang Terjadi di Desa Kayuapak - Afifah Novita Ramadhani; Siti Aisyiah (Universitas Muhammadiyah Surakarta, 2025)
Stunting is a significant health problem in Indonesia, especially in remote villages. This articleaims to maintain community awareness of the threat of stunting and increase the innovation of processed moringa leaves in Kayuapak Village through community empowerment by utilizing local potential, especially moringa leaves (Moringa oleifera). This activity was carried out through the Muhammadiyah Aisyiyah Community Service Program (KKNMAs) in Kayuapak Village, Sukoharjo, which focused on socialization, training, and processing of moringa-based products as a source of essential nutrients for children, adolescents and adults. The results showed an increase in community awareness of the importance of utilizing moringa leaves for stunting prevention as well as positive acceptance of moringa-based product innovations, such as donuts, onion sticks, and ice cream. Through this program, it is hoped that the stunting rate can continue to be reduced and public awareness of the importance of nutrition will increase.